Analisis Vegetasi Pada Tegakan Pinus merkusii Di Desa Rambusaratu Kecamatan Mamasa Provinsi Sulawesi Barat - M, Limerti; Idris, Andi Irmayanti; Ramli, Muhammad Agusfartham (Pangale Journal of Forestry and Environment, 2025)
Pinus merkusii is one of the important production forest species widely developed in the Forest area of ​​West Sulawesi. The strong dominance of pine often affects the vegetation structure and the level of diversity of understory plants. This study aims to describe the structure and composition of vegetation in Pinus merkusii stands and analyze the level of diversity and ecological role of each species in Rambusaratu Village, Mamasa District, West Sulawesi Province. The study used the species-area curve method with a quadratic plot system with a plot size of 20x20 m, a total of 18 plots were observed to obtain data on the number of species, number of individuals, density, frequency, dominance, and calculation of the Importance Value Index (INP), Shannon-Wiener diversity index (H’), evenness (E), and species richness (R). The results showed that there were 13 types of vegetation spread across four growth strata. Pinus merkusii had the highest INP value in the tree strata, indicating very strong dominance. The diameter distribution pattern did not form an inverted J curve, which indicates regeneration is dominated by trees with a medium class due to the simultaneous planting of pines in the study location. The diversity value (H') is low, indicating a community dominated by one species, while the evenness value (E) indicates an unbalanced distribution of individuals across species